Rotation–differential rotation relationships for late‐type single and binary stars from Doppler imaging. Issue 8 (22nd November 2017) - Kővári, Zs.; Oláh, K.; Kriskovics, L.; Vida, K.; Forgács‐Dajka, E.; Strassmeier, K. G.
Abstract : From our sample of spotted late‐type stars showing surface differential rotation, we find that the relationship between the rotation period and the surface shear coefficient α = ΔΩ/Ωeq is significantly different for single stars compared to members in close binaries. Single stars follow a general trend that α increases with the rotation period. However, differential rotation of stars in close binary systems shows much weaker dependence on the rotation, if any, suggesting that in such systems, tidal forces operate as a controlling mechanism of differential rotation.